1995
DOI: 10.1021/ic00117a003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Photoelectrochemical Studies on the 18-Molybdodisulfate Anion [S2Mo18O62]4-

Abstract: The heteropoly anion clusters [SzMoigOea]4-and [S2Moi8062]5may be photochemically activated to generate extremely powerful oxidants. Quantitative photoelectrochemical measurements using laser excitation at 325 nm of acetonitrile solutions of [S2M018O62]4containing the electron donors (ED), toluene and tetrahydrofuran, with hydrodynamic voltammetric monitoring at a platinum channel electrode are consistent with the following CECE mechanism: S2Mo,8062]4" + 2e" (E); ED+ (fast) --products. Photochemical oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 1 publication
(1 reference statement)
4
41
0
Order By: Relevance
“…where subscripts Ru, W, and RuW refer to [Ru(bpy) 3 the stability constant can be calculated from the ratio of the intercept:slope. This plot shows a graph that is initially linear and whose slope increases after the cation:anion ratio is less than 4.1:1.…”
Section: Results Andmentioning
confidence: 99%
See 2 more Smart Citations
“…where subscripts Ru, W, and RuW refer to [Ru(bpy) 3 the stability constant can be calculated from the ratio of the intercept:slope. This plot shows a graph that is initially linear and whose slope increases after the cation:anion ratio is less than 4.1:1.…”
Section: Results Andmentioning
confidence: 99%
“…[Ru(bpy) 3 ] 2+ in particular is deemed to be a suitable candidate due to its strong absorption in the visible region and its well-characterized photophysical properties. Recently, we demonstrated that [Ru(bpy) 3 4 In the present paper, we report the electronic and photophysical properties of the equivalent adducts formed in acetonitrile with the tungstate analogue [S 2 W 18 O 62 ] 4-. Again, strong electronic communication between the ions appears to be a feature of these ion clusters, but in contrast to the polymolybdate system, a relatively long-lived luminescent charge-transfer component is detected.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…425,426 Earlier electrochemical investigations had shown that reductions can proceed beyond the two-electron stage; a recent example is the behavior of [S 2 Mo 18 O 62 ] 4À which, like other molybdates, can be reduced by up to six electrons. 141,[427][428][429][430] Density functional theory calculations have been reported for Keggin anions treated as clathrates of XO 4 nÀ in a neutral M 12 O 36 shell; these provide satisfactory explanations for the relative stabilities of the a-and b-structures (see Table 8) and for the first reduction steps of 2, 2, and 2 electrons. 109,431 Several structure determinations of heteropoly blues have now been reported but, as expected, none can unambiguously locate the reduced metal centers.…”
Section: Reduction: Heteropoly Blues and Brownsmentioning
confidence: 97%
“…The products of reaction of organophosphonyl and organosilyl precursors with a variety of lacunary anions lead to a class of organic-inorganic hybrids, Table 28, that have been used for grafting into polymer matrices and the incorporation of magnetic nanoparticles. 428 …”
Section: Organometallic and Functionalized Derivativesmentioning
confidence: 99%